Holocene climatic evolution at the Chinese Loess Plateau: Testing sensitivity to the global warming-cooling events - Anwar, Taslima; Kravchinsky, Vadim A.; Zhang, Rui; Koukhar, Lioudmila P.; Yang, Lirong; Yue, Leping (Journal of Asian Earth Sciences, 2018)
A high resolution petromagnetic analysis demonstrates that pedogenic alterations in Holocene loess (sand) sequences from the regions of the Guanzhong Basin and the Mu Us Desert on the Chinese Loess Plateau (CLP) were affected by climatic variations in temperature and precipitation. Three warm-humid intervals (similar to 8.4-3.7, similar to 2.4-1.2, and similar to 0.81-0.48 ka), associated with soil formation and relatively high values of petromagnetic parameters, occurred during the Holocene. A substantial paleosol development from similar to 8.4 to 3.7 ka and higher petromagnetic parameter values indicate a generally strong warm-humid phase in the mid-Holocene which can be attributed to the Holocene climatic optimum. Our study demonstrates that the Holocene climate in the eastern part of the CLP is sensitive to warming and cooling events linked to global changes in temperature and precipitation. A complete Holocene climate record is constructed, correlating well with the other regional climate records along the south-to-north profile on eastern CLP, and suggesting that similar climatic changes occurred in eastern monsoonal China during the Holocene. Results are supported by other climate records in different regions of the world, and imply that the Holocene climatic optimum in the northern hemisphere probably took place at the same time.